Wideband Dielectric Feeder For K-Band Parabolic Antenna - Ahmad Zubir, Ihsan (2018)
Parabolic antennas are one of vital devices for long distance communication such as radio relay links and satellite links due to their high gain, high directivity and high power handling feature. In addition, hat feeder is widely used as a feeder for parabolic antennas due to low cross-polarization level, low sidelobes and low reflection coefficient. However, hat feeder has narrow bandwidth up to 30% which cannot be used in wideband application. This thesis describes the development and analysis of wideband feeder of parabolic antenna using dielectric resonator (DR) feeder. There are two designs of wideband dielectric resonator antenna (DRA) using stacked structure with two different shapes which are cylindrical and half cylindrical DRs are proposed in this work. The cylindrical DRs used RO4003C, FR4 and RO6010, while the half cylindrical DRs used alumina (Al2O3), silica (SiO2) and magnesium zirconate (MgZrO3). The stacked perforated DRA (SPDRA) achieved bandwidth of 75.8 % with the average gain of 5.65 dBi using perforated techniques, whereas the stacked half cylindrical DRA (SHCDRA) has bandwidth of 61.01% with the average gain range 4.885 dBi, with each of the half cylindrical are rotated by angle of 30'brelative to its neighboring layer. The bandwidth measurement results for SPDRA and SHCDRA designs show a reasonable agreement with different of 2.7% and 0.48%, respectively in comparison with simulation. Both of the proposed DRAs were mounted on the parabolic reflector and the average gain and 3 dB beamwidth are achieved 27.75 dBi, 27.08 dBi and 4.5' to 5.8 and 4.9' to 6.3' respectively. A parametric analysis is carried out to analyze and verify the characteristics of the proposed antennas by using Computer Simulation Technology (CST) software.